2006
DOI: 10.1086/501472
|View full text |Cite
|
Sign up to set email alerts
|

Human Serum Amyloid P Component Protects againstEscherichia coliO157:H7 Shiga Toxin 2 In Vivo: Therapeutic Implications for Hemolytic‐Uremic Syndrome

Abstract: Shiga toxin (Stx) 2 causes hemolytic-uremic syndrome (HUS), an intractable and often fatal complication of enterohemorrhagic Escherichia coli O157:H7 infection. Here, we show that serum amyloid P component (SAP), a normal human plasma protein, specifically protects mice against the lethal toxicity of Stx2, both when injected into wild-type mice and when expressed transgenically; in the presence of human SAP, there was greatly reduced in vivo localization of Stx2 to the kidneys, suggesting a possible mechanism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
52
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 17 publications
3
52
0
Order By: Relevance
“…Nevertheless, there is experimental evidence that SAP can contribute to host defense against certain bacterial infections (17). SAP neutralizes Stx2, but not Stx1, in vitro, and human SAP protects mice from Stx2-induced disease (14). The Stx2-neutralizing effect is not present in the sera of nonhuman species tested so far (15), consistent with the much higher binding avidity of human SAP than mouse SAP to other known ligands (18).…”
mentioning
confidence: 63%
See 2 more Smart Citations
“…Nevertheless, there is experimental evidence that SAP can contribute to host defense against certain bacterial infections (17). SAP neutralizes Stx2, but not Stx1, in vitro, and human SAP protects mice from Stx2-induced disease (14). The Stx2-neutralizing effect is not present in the sera of nonhuman species tested so far (15), consistent with the much higher binding avidity of human SAP than mouse SAP to other known ligands (18).…”
mentioning
confidence: 63%
“…Armstrong and colleagues identified SAP as a potential neutralizing factor (14). SAP is synthesized in the liver and circulates in the blood at levels of 8 to 55 mg/liter (42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, whether this accounts for the majority of clinical symptoms found in EHEC-associated HUS or not is still unknown, with the consequence that an effective therapy is as yet unavailable (5). Armstrong et al (6) have found that human serum amyloid P is binding to Stx2 and protecting mice against the lethal challenge by i.v. administered Stx2.…”
Section: H Emolytic Uremic Syndrome (Hus)mentioning
confidence: 99%
“…Strain % HEp-2 cells with adherent EPEC as described in a previous article (Armstrong et al, 2006), and the 125 I-bundlin was immediately separated from the reaction by-products using a 0.7 ¥ 15 cm Sephadex (GE HealthCare) G25 gel-filtration column. The protein concentration and specific activity (8.68 ¥ 10 5 cpm mg -1 ) of the 125 I-bundlin preparation were determined as described elsewhere (Armstrong and Peppler, 1987).…”
Section: Preparation Of Radio-iodinated Bundlin and Radio-receptor Bimentioning
confidence: 99%